Aplikasi Mobile Perpustakaan Berbasis Android (Studi Kasus Perpustakaan STMIK Palangka Raya) - Qamaruzzaman, M. Haris; Haris, Ferdiyani (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2016)
Android is an operating system for mobile devices based on Linux, versions of android is ever released Android version 1.1, Android version 1.5 (Cupcake) Android version 1.6 (Donut), the Android version 2.0 / 2.1 (Eclair), Android Version 2.2 ( Froyo or Frozen Yoghurt), and Android version 2.3 (Gingerbread). There is no problem of this research is to create a mobile application android-based library (library, case studies Palangkaraya Campus). This system aims to help students find the information collections, membership, books being borrowed and never borrowed, change passwords member, information libraries and librarians. The system is made using Eclipse, the Java programming language, PHP and MySQL as a media server that is accessed using the application The methods in this study includes data collection method (observation, literature, and interviews) and analyzed using analysis systems PIECES. Analysis PIECES have 6 (six) phases Performance, Information, Economics, control, efficiency and service. In this study has been conducted to test black box testing or testing program errors and the result of the program can be run to provide better information.